Multivalent Antibody‐Recruiting Macromolecules: Linking Increased Binding Affinity with Enhanced Innate Immune Killing. (10th July 2020) - Uvyn, Annemiek; De Geest, Bruno G.
Abstract: Antibody‐recruiting molecules (ARMs) are a novel class of immunotherapeutics. They are capable of introducing antibodies onto disease‐relevant targets such as cancer cells, bacterial cells or viruses. This can induce antibody‐mediated immune responses such as antibody‐dependent cellular cytotoxicity (ADCC), complement‐dependent cytotoxicity (CDC) and antibody‐dependent phagocytosis (ADCP), which can kill the pathogen. In contrast to the classic ARMs, multivalent ARMs could offer the advantage of increasing the efficiency of antibody recruitment and subsequent innate immune killing. Such compounds consist of multiple target‐binding termini (TBT) and/or antibody‐binding termini (ABT). Those multivalent interactions are able to convert low binding affinities into increased binding avidities. This minireview summarizes the current status of multivalent ARMs and gives insight into possible benefits, hurdles still to be overcome and future perspectives. Abstract : Into the line of fire : Macromolecular antibody recruiting molecules can bind though multivalent interaction with endogenous antibodies and draw these to the surface of target cells or pathogen, thereby marking the latter for innate immune destruction.